2007
DOI: 10.1139/v07-049
|View full text |Cite
|
Sign up to set email alerts
|

Concerted rate-limiting proton transfer to sulfur with nucleophilic attack at phosphorus — A new proposed mechanism for hydrolytic decomposition of the P=S pesticide, Diazinon, in moderately acidic sulfuric acid media

Abstract: We report herein the first kinetic study of a P=S containing organophosphorus pesticide, Diazinon (1), in the moderately concentrated acid region. Product analyses (31P NMR) show that reaction occurs only at the P centre. The rate-acidity profile (kobs vs. molarity of H2SO4) appears as a curve in which the initial slight downward trace (molarity = 1 to ca. 5) is followed by sharper upward curve (molarity ca. 5 to 14). Using treatments involving the excess acidity (X) method, the A-1 and A-2 mechanistic possibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…31 P NMR spectra of the starting triesters as well as that of the authentic trimethyl phosphate and trimethyl phosphorothioate in methanol were used as references (the chemical shifts of the known compounds in CD 3 OD were referenced using an inserted sealed glass tube containing ~0.1 M phosphoric acid in CD 3 OD). A competitive demethylation process, resulting from a nucleophilic attack on one of the CH 3 groups to form X═P(OR)(OCH 3 )(O − ), was observed for substrates 1n , o and 2m , n , p under basic conditions in methanol. The reaction progress was monitored by determining both the % conversion of the starting triester and the ratios of the P–OLg cleavage product (trimethyl phosphate/phosphorothioate triester) to the demethylation product (a diester).…”
Section: Methodsmentioning
confidence: 97%
“…31 P NMR spectra of the starting triesters as well as that of the authentic trimethyl phosphate and trimethyl phosphorothioate in methanol were used as references (the chemical shifts of the known compounds in CD 3 OD were referenced using an inserted sealed glass tube containing ~0.1 M phosphoric acid in CD 3 OD). A competitive demethylation process, resulting from a nucleophilic attack on one of the CH 3 groups to form X═P(OR)(OCH 3 )(O − ), was observed for substrates 1n , o and 2m , n , p under basic conditions in methanol. The reaction progress was monitored by determining both the % conversion of the starting triester and the ratios of the P–OLg cleavage product (trimethyl phosphate/phosphorothioate triester) to the demethylation product (a diester).…”
Section: Methodsmentioning
confidence: 97%
“…The k 0,ASE2 rate constants deduced for the rate-determining step at several temperatures are given in Table . To our knowledge, no upper limit for the k 0,ASE2 value has in principle been reported in literature for the wide variety of reactions that follow the A-S E 2 mechanism. , …”
Section: Resultsmentioning
confidence: 95%
“…To our knowledge, no upper limit for the k 0,ASE2 value has in principle been reported in literature for the wide variety of reactions that follow the A-S E 2 mechanism. 22,[38][39][40] The mechanism put forward is outlined in Scheme 1. In a previous work, we calculated the dissociation constant pK SH 2+…”
Section: Resultsmentioning
confidence: 99%
“…In this study we have found that the OP simulants, aryl diphenylphosphinothioates, reacted with hydroxide, as nucleophile, via an S N 2(P) mechanism. Of the environmental pathways for degradation of OP neurotoxins, including photochemical and microbial routes, hydrolysis remains a major abiotic contributor to OP decomposition. Water is, of course, the ubiquitous solvent and nucleophile, and under alkaline conditions (eg, calcareous fresh waters) hydroxide is the major environmental nucleophile.…”
Section: Resultsmentioning
confidence: 99%
“…Under such optimal conditions impressive catalytic enhancements for methanolysis of OP pesticides have been reported, ranging from 20,000‐fold to millions‐fold, and to billion‐fold with La 3 + (bridged methoxide lanthanum dimers) and from million‐fold to 100 billion‐fold with Cd 2 + , Mn 2 + , and a Pd 2 + complex . The effect of sulfuric acid media for decomposition of the organophosphorothioate insecticide, diazinon, gives significant acceleration of decomposition relative to pure water …”
Section: Introductionmentioning
confidence: 99%